L-shaped relationship between dietary vitamin E intake and migraine in adults: a cross-sectional analysis of NHANES 1999–2004 - Wangchun Wu; Yanguo Peng; Shuiyu Chen (Frontiers in Neurology)
BackgroundSeveral previous studies have suggested that micronutrients with antioxidant properties are protective factors against migraine. Despite being an important dietary antioxidant, the relationship between dietary vitamin E and migraine has not been extensively studied. This study sought to understand the association between dietary vitamin E intake and the incidence of migraine.MethodsData from the National Health and Nutrition Examination Survey (1999–2004) were used in this cross-sectional analysis. To assess the association between dietary vitamin E intake and migraine, we employed logistic regression, restricted cubic spline regression, and stratified analyses.ResultsThis study included 10,063 participants who were 20 years old or older, 20.1% (2018/10,063) of whom reported suffering from migraine. Compared with the lowest vitamin E intake T1 (<4.5 mg/day), the adjusted odds ratios (ORs) of dietary vitamin E intake and migraine for T2 (4.5–7.8 mg/day) and T3 (>7.8 mg/day) were 0.85 (95% confidence interval [CI]: 0.74–0.98, p = 0.03) and 0.75 (95% confidence interval [CI]: 0.63–0.90, p = 0.001), respectively. An L-shaped nonlinear association existed between dietary vitamin E consumption and migraines (p = 0.006). For participants who consumed <7.3 mg of vitamin E daily, the OR for migraine was 0.92 (95% CI: 0.874–0.969, p = 0.0015). When daily vitamin E intake was ≥7.3 mg/day, the risk of migraine did not continue to decrease with increasing dietary vitamin E consumption (OR, 1.008; 95% CI, 0.984–1.033). The results of the sensitivity analysis suggest that the association between dietary vitamin E intake and migraine remains robust.ConclusionIn adults, the association between dietary vitamin E intake and migraine is an L-shaped curve (nonlinear, p = 0.006), with an inflection point at 7.3 mg/day. It reminds individuals to keep diets balanced.